Urgensi Pengembangan Akad Musyarakah sebagai Inovasi Produk Pembiayaan Produktif BMT di Lingkungan Kampus - Maulani Salsabila; Cucu Susilawati (Program Studi Hukum Ekonomi Syariah, 2026)
This research is motivated by the limited access to productive financing faced by academics in the university environment, while the financing products available at Baitul Māl Wat Tamwīl (BMT) in the campus environment are still dominated by consumptive contracts and have not accommodated partnership-based financing. This condition raises the need for the development of a fairer and more sustainable sharia financing model. The problem studied in this study is how urgent is the urgency of developing musyarakah contracts as an innovation of BMT productive financing products in the campus environment and its relevance for the empowerment of the academic community. The research method used is a literature study with a qualitative-descriptive approach through the analysis of the literature on sharia economic law, related regulations, and previous studies on BMT and musyarakah contracts. The results of the study show that the musyarakah contract has great potential to be developed as a productive financing product for BMT in the campus environment because it emphasizes the principle of partnership and proportional risk sharing. The development of musyarakah contracts is considered to be able to be an alternative financing that supports the entrepreneurship of the academic community and strengthens the role of campus BMT in an inclusive and sustainable Islamic financial ecosystem.